Home childbirth among young mothers aged 15–24 years in Nigeria: a national population-based cross-sectional study - Asa Auta; Emmanuel O Adewuyi; Vishnu Khanal; Yun Zhao; Lungcit David; Olasunkanmi David Bamidele (BMJ Open)
Objective To estimate the prevalence and identify factors associated with home childbirth (delivery) among young mothers aged 15–24 years in Nigeria.Design A secondary analysis of cross-sectional data from the 2013 Nigeria Demographic and Health Survey (NDHS).Setting Nigeria.Participants A total of 7543 young mothers aged 15–24 years.Outcome measure Place of delivery.Results The prevalence of home delivery among young mothers aged 15–24 years was 69.5% (95% CI 67.1% to 71.8%) in Nigeria—78.9% (95%CI 76.3% to 81.2%) in rural and 43.9% (95%CI 38.5% to 49.5%, p<0.001) in urban Nigeria. Using the Andersen’s behavioural model, increased odds of home delivery were associated with the two environmental factors: rural residence (adjusted OR, AOR: 1.39, 95% CI 1.06 to 1.85) and regions of residence (North-East: AOR: 1.97, 95% CI 1.14 to 3.34; North-West: AOR: 2.94, 95% CI 1.80 to 4.83; and South-South: AOR: 3.81, 95% CI 2.38 to 6.06). Three of the enabling factors (lack of health insurance: AOR: 2.34, 95% CI 1.16 to 4.71; difficulty with distance to healthcare facilities: AOR: 1.48, 95% CI 1.15 to 1.88; and <4 times antenatal attendance: AOR: 3.80, 95% CI 3.00 to 4.85) similarly increased the odds of home delivery. Lastly, six predisposing factors—lack of maternal and husband’s education, poor wealth index, Islamic religion, high parity and low frequency of listening to radio—were associated with increased odds of home delivery.Conclusions Young mothers aged 15–24 years had a higher prevalence of home delivery than the national average for all women of reproductive age in Nigeria. Priority attention is required for young mothers in poor households, rural areas, North-East, North-West and South-South regions. Faith-based interventions, a youth-oriented antenatal care package, education of girls and access to health insurance coverage are recommended to speed up the reduction of home delivery among young mothers in Nigeria.